Memories and news about the Ercilla-Zuñiga family andits links with the Valvanera monastery (Berceo, 2025)
This journal has previously dealt with the relationship between the family of Alonso de Ercilla y Zúñiga and the Valvanera Monastery. This article revisits this subject providing some new documentation. Special attention is paid to the generation before the poet, especially to the figure of his father, as well as to the generation immediately after him. Finally, some unsuccessful attempts to find the family remains in the monastery are reviewed.
Keywords: Array; Array; Array; Array